Pitfalls and perils of financial innovation: The use of CDS by corporate bond funds - Tim Adam; André Güttler (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2015)
We use the financial crisis of 2007-2009 as a laboratory to examine the costs and benefits of teams versus single managers in asset management. We find that when a fund uses complex trading strategies involving the use of CDS team-managed funds outperform solo-managed funds. This may be due to the greater diversity of expertise, experience and skill of teams relative to single managers. During the financial crisis, however, the performance premium of teams becomes negative, which may be because of the slower decision times of teams, which are especially costly during times of rapidly changing market conditions.
Keywords: G11; G15; G23; 330; mutual funds; management teams; financial crisis; credit default swaps; performance; market timing